Congenital adrenal hyperplasia is a very rare cause of adrenal incidentalomas in Sweden - Sahlander, Fredrik; Bensing, Sophie; Falhammar, Henrik (Frontiers in Endocrinology, 2022)
Background Undiagnosed congenital adrenal hyperplasia (CAH) can cause adrenal incidentalomas, but the frequency is unclear. Objectives This study aimed to investigate the prevalence of CAH in a population with adrenal incidentalomas and report the clinical characterization. Material and methods This was a prospective study performed at a regional hospital from 2016 to 2021. Patients with adrenal incidentalomas were investigated with an adrenocorticotropic hormone (ACTH)-stimulation test in addition to hormonal workup. Serum cortisol and 17-hydroxyprogesterone (17OHP) were analyzed. Individuals with a basal or stimulated 17OHP ≥30 nmol/L were classified as suspicious non-classic CAH, and a CYP21A2-gene analysis was performed in these subjects. Results In total, 320 individuals with adrenal incidentalomas were referred to the center, and of these individuals, an ACTH-stimulation test was performed in 222 (median age, 67 (24–87) years; 58.6% women; and 11.7% with bilateral lesions). None of the individuals presented a basal 17OHP ≥30 nmol/L, but there were 8 (3.6%) who did after ACTH stimulation. Four of these subjects (50%) presented bilateral lesions, and the tumor size was larger compared to that of the individuals with a stimulated 17OHP <30 nmol/L (median, 38 (19–66) vs. 19 (11–85) mm, p=0.001). A CYP21A2 variation (p.Val282Leu) was detected in one of the eight subjects with a stimulated 17OHP ≥30 nmol/L, i.e., the patient was a heterozygotic carrier. None of the eight subjects presented with cortisol insufficiency or clinical signs of hyperandrogenism. Conclusions The prevalence of non-classic CAH in an adrenal incidentaloma cohort was 3.6% based on stimulated 17OHP and 0% based on gene analysis. CAH should be considered in AI management in selected cases and confirmed by genetic analysis.